Development of an Industrial Electrical Installation Training Unit - Yuniarti, Nurhening; Taruno, Djoko Laras Budiyo; Ali, Muhamad; Sukisno, Toto; Muhfizaturrahmah, Muhfizaturrahmah (DPTE FT UNY, 2023)
The purpose of this study is to obtain a modular unit for training and instruction in industrial electrical installations as a suitable learning media. This study uses research and development (R&D) with ADDIE model, which consists of five phases: analysis, design, development, implementation, and evaluation. The research subject is Diploma 4 student in Department of Electrical Engineering Education, Faculty of Engineering, Universitas Negeri Yogyakarta. The research result as follows. (1) Manufacture of industrial electrical equipment training module products. (2) Application program feasibility for material-related assessment includes content aspects, learning aspects, and efficiency aspects. All aspects of the substantive feasibility study were rated as highly feasible with a score of 94.5 points. Application program feasibility for media professional evaluation includes visual, hardware, usability, and portability aspects. It has an average score of 109.5 on all aspects of the media feasibility test and is categorized as highly feasible. (3) Student user reactions, including learning, visual, hardware, usability, and portability. All aspects of student user response were rated as very good with an average score of 107.1.